The Influence of Workload, Motivation, and Work Environment on Generation Z Employee Productivity in Cikarang - Kelani, Sofia; Dwianto, Agung Surya (Yayasan Sinergi Kawula Muda, 2026)
This study analyzes the influence of workload, work motivation, and work environment on the work productivity of Generation Z employees in the Cikarang manufacturing industry. This phenomenon is important given the unique characteristics of Generation Z, which now dominates the labor market amid demands for industrial efficiency. Using an associative quantitative approach, with purposive sampling techniques involving 240 Generation Z respondents, primary data was collected through questionnaires. Measurement accuracy was ensured using Pearson's corrected item-total correlation for validity (r ≥ 0.30) and Cronbach's alpha for reliability (α ≥ 0.60 for exploratory adaptation). Furthermore, before testing the hypothesis through multiple linear regression, all essential diagnostic assumptions, including residual normality, multicollinearity (Tolerance and VIF), and heteroscedasticity, were strictly met. The results indicate that workload and work motivation are significantly associated with employee productivity. Workload, when appropriately managed, may support productivity, while work motivation is associated with maintaining consistent performance in a target-oriented work environment. In contrast, the work environment does not show a statistically significant relationship with productivity in this study. This finding suggests that, within this specific context, the work environment may function as a supporting condition rather than a direct determinant of productivity. Simultaneously, these three variables have a significant effect with a contribution of 54.1%. This study concludes that Generation Z's work productivity is more closely related to optimal work volume and motivation than to physical environmental facilities.